Regulatory Intelligence in Emerging Pharma Markets: Bridging Innovation with Compliance - Mirzapure, Isha Anil; Deshmukh, Manish; Bhange, Manjusha; Salve, Yash Manoj; Dandekar, Mayur Rajeshwar (International Journal of Pharmaceutical Investigation, 2026)
The delayed access to innovative medicinal products such as orphan drugs and biologics and mRNA vaccines and advanced therapy medicinal products ATMPs occurs in numerous developing nations because of disjointed regulatory frameworks and inadequate infrastructure and minimal harmonization efforts. The strategic process of Regulatory Intelligence (RI) which entails real-time collection and analysis of global regulatory insights functions now as a bridge to speed up market entry. This analysis evaluates the developing significance of RI as a tool for enhancing rapid and secure regulatory procedures which maintain transparency within Low- and Middle-Income Countries (LMICs) that experience substantial neglect diseases and new health challenges. We detail worldwide RI strategy approaches through an examination of their implementation towards delivering therapeutic treatment for high priority areas. Through a study of regulatory structures and capacity-building methods and asset-based pharmaceutical systems we establish major obstacles and facilitators to Integration of Regulatory Innovation. The paper provides detailed insights regarding how RI affects the development of expedited pathways together with Real-World Evidence (RWE) methods and adaptive licensing practices and collaborative review procedures. Multiple real-world examples from Asian, African and Latin American regions demonstrate how RI drives enhancements in both regulatory speed and public health service delivery. A step-by-step guide is provided to resolve infrastructural and human capital challenges and policy inconsistencies so LMICs can properly implement RI in their regulatory framework. The document provides specific policy suggestions that combine regulatory convergence with digital development and stakeholder relations and openness. The findings from this review demonstrate that RI operates beyond being a practical mechanism by establishing the core element needed in resilient regulatory frameworks which also include inclusivity and future-readiness. Investment in RI by LMICs enables them to boost regulatory performance and establishes their stronger strategic positions within the global pharmaceutical sphere which ensures fair access of innovative healthcare to all populations.
Keywords: Regulatory Intelligence (RI); Accelerated access; Orphan drugs; Biologics; mRNA vaccines; Advanced Therapy Medicinal Products (ATMPs); Developing countries; Regulatory harmonization.